Elasticity and competitiveness of Indonesia’s palm oil export in India market - Awan Setya Dewanta; Riza Noer Arfani; Erfita Erfita (Economic Journal of Emerging Markets, 2016)
This study examines the elasticity and competitiveness of Indonsia’s palm oil export in the India market, 1990 -2014. The methods used are Error Correction Model (ECM) and Revealed Comparative Advantage (RCA) approach. The results shows that the price is inelastic in short-term but it is elastic in long-term. The income and exchange rate are elastic in the long-term. There is also a decline in competitiveness in the market India. These findings also demonstrate that palm oil is normal goods and can be easily substituted with the same products of other countries or other vegetable oils. It threatens the Indonesian palm oil competitiveness in the Indian market.